Prevalence of depression and anxiety among working women in Saudi Arabia: psychosocial and perinatal correlates - Deemah AlAteeq; Shouq Mohammed AlNujaim; Abdullah H. AlGharbi (BMC Women's Health)
Abstract Background Women comprise a sizeable portion of the workforce in various industries. They might face many challenges that affect their mental well-being. Hence, a study that addresses working women’s psychosocial and perinatal aspects mandates the necessity to fill the void and deficiencies related to clinical research. Objectives To explore the prevalence of depression and anxiety among working women in Saudi Arabia and its psychosocial and perinatal correlations. Methods This cross-sectional study involved 580 working women from Riyadh, Saudi Arabia, who participated via convenience sampling. An online-based questionnaire was used to collect data, including sociodemographic, occupational, medical, and perinatal data. The Patient Health Questionnaire (PHQ-9) and Generalized Anxiety Disorder 7 (GAD-7) were used to assess depression and anxiety. Results More than half (56.4%) had a pregnancy history, half of them took maternity leave (49%), and most needed additional leave (65.2%). Half of the participants had mild to moderate levels of depression and anxiety, 50.2% and 49%, respectively. A positive correlation was found between depression and anxiety (p-value = < 0.001). Participants who drank alcohol or had a lower mean score of total pregnancies had a significantly higher prevalence of moderately severe to severe depression (p = < 0.05). And smokers had a significantly higher rate of severe anxiety (p = < 0.01). Participants previously diagnosed with a psychiatric disorder displayed a higher risk of severe depression and anxiety (p < 0.001). Conclusion The findings of this study highlight the significant prevalence of mild to moderate level of depression and anxiety among working women in Saudi Arabia and their strong association with various psychosocial and perinatal factors. These results underline the urgent need for comprehensive mental health support and interventions tailored to the unique challenges faced by working women in the region.